Strategi Quadruple Helix Dalam Meningkatkan Ekonomi Masyarakat Kelompok Cari Lidi (Carli) di Kecamatan Sungai Kanan Kabupaten Labuhanbatu Selatan - Ashabul jannah siregar; Fauzi Arif Lubis; Nuri Aslami (Transformasi: Journal of Economics and Business Management, 2023)
Business activities are generally carried out by the community by exploiting the natural potential around them, namely the business of utilizing palm oil stick waste. This waste has not been used at all by the community so it is left like that. However, the existence of a search for sticks can provide additional income for the community. This research aims to find out the strategy for implementing the Quadruple Helix in improving the economy of the people of the search for sticks (carli) group in Sungai Kanan District, South Labuhanbatu Regency. The Quadruple Helix implementation strategy is one model that is suitable for social research and innovation. Data collection was carried out using a qualitative research design through observation, documentation and in-depth interviews, then supported by literature study. The research results show that the strategy for implementing the Quadruple Helix in improving the community's economy can provide significant benefits if implemented well. There are several ways to implement the Quadruple Helix so that it can help improve the economy of the people of South Labuhanbatu Sungai Kanan District, such as Partnership and Collaboration. Through partnerships between government, academics, business and society, different resources and knowledge can be combined. This collaboration can produce innovations and new solutions to increase production, added value of stick products, and the number of stick exports, thereby providing greater economic benefits for the stick-seeking (carli) community. However, there are several obstacles in implementing the Quadruple Helix, namely that even though it has been implemented, it has not been fully implemented to the maximum extent for the people of Sungai Kanan Labuhan Batu Selatan District.